Optimalisasi Platfrom E-commerce Dalam Pemasaran tanjak PalembangPlatfrom Digital: Tokopedia, Bukalapak, Blibli - Sandra Sandra; Lismita Maharani; Intan Dwi Lestari; Maya Panorama (Pusat Riset dan Inovasi Nasional, 2025)
Tanjak Palembang, as a cultural heritage typical of South Sumatra, has high historical and aesthetic value. Although it was once only worn by the nobility, now tanjak has become part of the cultural identity that can be worn by anyone. In the digital era, marketing of traditional cultural products such as tanjak faces challenges from modern products and consumer accessibility. This study aims to analyze the optimal strategy in utilizing e-commerce platforms, such as Tokopedia, Bukalapak, and Blibli, to increase the appeal, sales, and preservation of the Palembang tanjak culture. The research method used is qualitative descriptive, with primary data collection through interviews and observations, as well as secondary data from literature and industry reports. The results of the study indicate that the use of e-commerce platforms significantly expands market reach and increases brand awareness of the Palembang tanjak. However, business actors also face challenges such as tight price competition and lack of knowledge in digital marketing. Therefore, the right strategy is needed, including training for MSMEs and improving the quality of digital content. Overall, e-commerce optimization has proven effective in increasing the marketing of Palembang tanjak, with the hope of collaboration between business actors, the government, and e-commerce platforms to support the development of local products.